Impact of COVID-19 on Dental Students' Psychological Health: Dampak COVID-19 terhadap Kesehatan Psikologis Mahasiswa Kedokteran Gigi. - Maryam Hameed Alwan (Academia Open, 2023)
This study investigates the psychological impact of the COVID-19 pandemic on dental students at Baghdad University College of Dentistry. Conducted between December 2021 and January 2022, this cross-sectional survey aligns with ethical guidelines and the Helsinki Declaration. The study utilized Cochran's equation to determine a sample size of at least 400, ensuring a 95% confidence level with a 5% margin of error. The Perceived Stress Scale (PSS) and the Covid Student Stress Questionnaire (CSSQ) were employed as primary tools, assessing general and COVID-19-related stress, respectively. A total of 411 students participated, with 67.50% experiencing moderate to severe stress (PSS <14) and 58.8% reporting average levels of COVID-related stress (CSSQ <7). Notably, there was a significant positive correlation between the PSS and CSSQ scores (P = 0.008). The analysis, conducted using IBM SPSS Statistics software V26, included descriptive statistics, Cronbach's alpha for reliability, and Pearson Correlation for assessing correlations. The findings indicate that a substantial proportion of dental students experienced heightened stress levels, potentially leading to mental health disorders like cognitive impairment. These results emphasize the need for universities to enhance psychological support and for government bodies to implement comprehensive health education and awareness programs. This study not only sheds light on the immediate psychological effects of the pandemic on dental students but also serves as a foundational reference for future interventions aimed at reducing stress levels in this demographic. Highlights: Dental students have experienced significant psychological impacts from the COVID-19 pandemic. The pandemic has caused increased stress, anxiety, and depression among dental students. Remote learning and decreased clinical experience have contributed to the negative psychological effects. Providing social and emotional support is important in mitigating the psychological impact of the pandemic on dental students. Keywords: COVID-19, SARS-CoV-2, Student, Dental, Stress